Asenapine treatment and health-related quality of life in patients experiencing bipolar I disorder with mixed episodes: post-hoc analyses of pivotal trials. (April 2014) - Michalak, E. E.; Guiraud-Diawara, A.; Sapin, C.
Abstract Objective: To evaluate the baseline impact of episode type (manic vs. mixed), defined using DSM-IV-TR criteria, in bipolar I disorder (BD-I) on health-related quality of life (HRQoL), and to investigate the differential effect of asenapine vs. placebo and olanzapine on HRQoL in BD-I patients with mixed episodes. Methods: In two identically designed 3 week, randomized, double-blind, flexible-dose, placebo- and olanzapine-controlled trials of asenapine, HRQoL was assessed using the 36-item Short-Form Health Survey (SF-36v2) administered at baseline and endpoint. In addition to evaluating the impact of clinical presentation (manic vs. mixed episodes) on baseline HRQoL, the impact of treatment intervention on HRQoL was assessed via analysis of covariance models at study endpoint, with center and treatment-by-diagnosis interaction as fixed effect and baseline score as covariates. Results: A total of 960 BD-I patients (asenapine: 372; olanzapine: 391; placebo: 197) were included in the two studies. The observed burden of disease on HRQoL was substantial compared to general US population norms, particularly in patients experiencing mixed episodes. The greatest impairments were observed in the mental domains of HRQoL (Mental Component Summary scores: mixed = 31.9; manic = 42.8). For patients with mixed episodes, when compared to olanzapine, asenapine treatment was associated with improvements noted in every domain, which did not reach statistical significance except for Vitality (asenapine = 55.0, olanzapine = 51.3; p = 0.014) and Role–Emotional (asenapine = 44.8, olanzapine = 40.3; p = 0.020). Compared to placebo patients with mixed episodes, asenapine treatment provided significant improvements (p < 0.05) in Bodily Pain (asenapine = 50.9, placebo = 45.9), Social Functioning (asenapine = 44.1, placebo = 39.6) and Mental Health (asenapine = 46.6, placebo = 42.7) by Week 3; by comparison, olanzapine treatment did not lead to significant improvements in any domain of HRQoL compared to placebo. Conclusions: Post-hoc analyses of two trials showed that BD-I patients with mixed episodes reported considerable impairments in HRQoL compared to patients with manic episodes. At 3 weeks, in patients with mixed episodes, asenapine was shown to lead to significant improvements in HRQoL compared to olanzapine and placebo. Results from these post-hoc analyses should be confirmed in prospective studies. Trial registration: NCT00159744, NCT00159796.